2001
DOI: 10.1159/000046966
|View full text |Cite
|
Sign up to set email alerts
|

Newly Developed Immobilized Polymyxin B Fibers Improve the Survival of Patients with Sepsis

Abstract: Background: Sepsis and septic shock are still major causes of morbidity and mortality in spite of the availability of powerful and broadly active antibiotics. Methods: A prospective, open and randomized trial of the effect of immobilized polymyxin fibers (PMX-F) on the survival of patients with sepsis throughout a follow-up period of 28 days or until discharge, if earlier, was carried out. Ninety-eight patients were included who met at least 4 of the criteria for systemic inflammatory response syndrome due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 27 publications
2
72
0
Order By: Relevance
“…8 PMX-DHP decreases the blood levels of cytokines and improves hemodynamics, 9 so PMX-DHP not only removes endotoxin, but also other cytokines and thus improves the hemodynamics of patients with septic shock. There are many reports of improved clinical symptoms and outcome achieved by PMX-DHP therapy in the septicemic patient, 10 but without clear evidence of its efficacy. A recent pilot study showed that PMX-DHP improved the left ventricular stroke work index, 11 providing further evidence that PMX-DHP improves the hemodynamics of patients in septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…8 PMX-DHP decreases the blood levels of cytokines and improves hemodynamics, 9 so PMX-DHP not only removes endotoxin, but also other cytokines and thus improves the hemodynamics of patients with septic shock. There are many reports of improved clinical symptoms and outcome achieved by PMX-DHP therapy in the septicemic patient, 10 but without clear evidence of its efficacy. A recent pilot study showed that PMX-DHP improved the left ventricular stroke work index, 11 providing further evidence that PMX-DHP improves the hemodynamics of patients in septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…In an animal model of sepsis, PMX improves oxygenation through the suppression of nitric oxide production (21). Kushi (26). A recent paper has suggested that more frequent applications will be effective against severe sepsis (27).…”
Section: F I G U R E 5 T H E C H E S T I Ma G E S O F T H E P a T Imentioning
confidence: 99%
“…Mortality of these patients with acute exacerbation has been reported to be high during their hospitalization (4)(5)(6). (9)(10)(11) (8,9,13 i g u r e 1 . S e r i a l Aa DO2 a n d s e r u m L DH v a l u e s p r e -a n d p o s t -P MX t r e a t me n t ( c a s e s 1 -6 ) .…”
Section: Idiopathic Interstitial Pneumonias (Iips) Represent a Heteromentioning
confidence: 99%